La casbah d’Alger Revitalisation du secteur sidi ramdhan Projet : Un Centre de savoir-faire traditionnel - KHOUCHANE, Sabrina; Mr CHORFI, Khaled (Encadreur) (Université Ferhat Abbas Sétif 1. Institut d'architecture et sciences de la terre. Département d'architecture, 2015)
Algeria is a rich country in terms of urban and architectural heritage in particular by the presence of a large traditional fabric, The heritage reflecting the identity and civilization of the inhabitants has faced problems of adaptation and integration to life and the contemporary requirements. One such wealth, the medina of Algiers, which has seen many past civilization (Roman, Ottoman, colonial, colonial .ect post ...) the cultural and civilizational footprint still exists, but suffers like most historical center of the abandonment and degradation is increasing, this danger not only to their physical dimension but also their social, economic and functional. Given the historical, cultural, architectural and memorial of Sidi Ramdhane sector, we have chosen it as a living example of the rich heritage, its analysis has allowed us to clearly know the real reasons for the damage and show the potential of the sector , and the historic city in general, in order to sensitize people about the value of our heritage and try to give them a different view on its importance and the need for its protection. It also allowed us to try to return the city to the rest of the historic center; reinstatement to the rest of the city will result in the improvement of living conditions.
الجزائر بلد غني من حيث التراث العمراني والمعماري وخاصة عن طريق وجود النسيج التقليدي واسع، هذا التراث الذي يعكس هوية وحضارة الساكنين به في مواجهة مع مشاكل التكيف والاندماج في الحياة الحالية ومتطلبات العصر. واحدة من هذه الثروة، قصبة الجزائر العاصمة، التي شهدت العديد الحضارة السابقة )الرومانية والعثمانية، الاستعمار الفرنسي آخر. إلخ ...( تلك البصمة الثقافية والحضارية لا تزال موجودة، الا ان القصبة كمعظم باقي المراكز التاريخية تعاني التهميش و التدهور الآخذ في الازدياد، هذا الخطر ليس فقط مت الجانب المادي بل يمس أيضا الحياة الاجتماعية والاقتصادية. ونظرا للأهمية التاريخية، الثقافية، المعمارية والتذكارية لقطاع سيدي رمضان بالقصبة، فقد اخترناه كمثال حي على التراث الغني، الدراسة التاريخية والمورفولوجية والاقتصادية له سمحت لنا بمعرفة بوضوح الأسباب الحقيقية للضرر وإظهار إمكانيات القطاع بشكل خاص والمدينة التاريخية بشكل عام، من أجل توعية الناس حول قيمة تراثنا ومحاولة إعطائهم وجهة نظر مختلفة على أهميتها وضرورة حمايتها. كما سمح لنا باقتراح إعادة ضم المدينة إلى بقية المركز التاريخي. إعادة الادماج مع بقية المدينة يؤدي إلى تحسين الظروف المعيشية.
Keywords: Patrimoine; Identité; Casbah d’Alger; Réintégration; Protection; Centre historique; Richesse patrimoniale